Reliabilty and Cost Benefit Analysis of DG Integrated Distribution System - Ch.V.S.S. Sailaja; P.V.N. Prasad (Bulletin of Electrical Engineering and Informatics, 2016)
Integration of Distributed generation (DG) results in a number of advantages ranging from reduction in losses to delayed generation and transmission capacities. In this paper the impact of DGs on reliability is considered and their effect on reliability in terms of number and location is evaluated. The integration of DG changes configuration of the radial system. This point is considered for evaluating the load point indices. The cost effectiveness of number of DGs is evaluated for the determining the returns on the DG investment cost. The above analysis is carried out on a RBTS Bus 2 system. The reliability indices are calculated using FMEA technique.